Curcumin nanoparticles incorporated in PVA/collagen composite films promote wound healing - Leng, QingQing (Drug Deliv, 2020)
Skin repair remains a common problem in plastic surgery. Wound dressing plays an important role in promoting local skin healing and has been widely studied. This study aimed to manufacture a composite film (CPCF) containing curcumin nanoparticles, collagen, and polyvinyl alcohol (PVA) to effectively promote the healing of skin wounds. Sustained drug release from the composite film provides long-term protection and treatment for skin wounds. Both antibacterial property and good histocompatibility of the CPCF were examined by analyzing antibacterial activity and cytotoxicity to validate its applicability for wound management. Moreover, in vivo studies proved that the CPCF had a rapid healing rate of 98.03%±0.79% and mature epithelialization on day 15 after surgery. Obvious hair follicles and earlier re-epithelialization was also noticed in the CPCF group using H&E staining. The result of Masson’s trichrome staining confirmed that CPCF could promote the formation of collagen fibers. In summary, CPCF may be promising as a wound dressing agent in wound management owing to its rapid wound-healing effects.